The Role of Environmental Risk Perception as a Mediator in the Relationship Between Eco-Anxiety and Pro-Environmental Behavior Among Generation Z in Lampung - Sri Ilham Nasution; Rahmad Purnama; Violla Dwi Puspita (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
Exposure to environmental issue–related information may enhance moral awareness, encouraging individuals to act in environmentally responsible ways. However, psychological factors such as eco-anxiety are often required to strengthen the intention to engage in pro-environmental behavior. This study examines whether eco-anxiety contributes to pro-environmental behavior among Generation Z in Lampung through the mediating role of environmental risk perception. Using a purposive sampling technique, data were collected from 305 Generation Z respondents (aged 13–28 years). This study employed a quantitative approach and used SEM-PLS for data analysis, with model fit criteria assessed using SRMR and NFI. The results show that: (1) eco-anxiety has a significant effect on environmental risk perception (p = 0,000; t = 12.718), (2) eco-anxiety has a significant effect on pro-environmental behavior (p = 0,000; t = 5.434), (3) environmental risk perception has a significant effect on pro-environmental behavior (p = 0,000; t = 5.994), and (4) environmental risk perception significantly mediates the relationship between eco-anxiety and pro-environmental behavior (p = 0,000; t = 5.117).